Spor yapan ve yapmayan ortaokul öğrencilerinin duygusal zekâ düzeyleri, öğrenme stilleri, dikkat ve öz-yeterliklerinin incelenmesi - Ayrancı, Mert (Bartın Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Bu araştırmanın amacı; Spor yapan ve yapmayan ortaokul öğrencilerinin duygusal zekâ düzeyleri, öğrenme stilleri, dikkat ve öz-yeterliklerinin incelenmesidir. Araştırmanın evrenini, T.C. Milli Eğitim Bakanlığı, Kastamonu İl Milli Eğitim Müdürlüğü'nün kapsama alanında bulunan ortaokul öğrencileri oluşturmaktadır. Araştırmanın örneklem grubunu ise evren içerisinden olasılığa dayalı olmayan örnekleme yöntemlerinden kolayda örnekleme yöntemi ile Şehit Osman Yılmaz Ortaokulu, Şehit Necmi Yıldırım Ortaokulu, Şehit Ayşe Aykaç Yatılı Bölge Ortaokulu, Şehit Ensar Ayanoğlu Ortaokullarında 2021-2022 eğitim öğretim yılında bu okullarda okuyan 6,7 ve 8. sınıf öğrencileri oluşturmaktadır. Elde edilen bu bilgiler ışığında araştırmanın örneklemi: 2021-2022 eğitim-öğretim yılında 6,7 ve 8. sınıfta öğrenim görmekte olan 926 öğrencinin içinden, kolayda örnekleme yöntemi ile seçilen 394 öğrenciden oluşmaktadır. Araştırmanın veri toplama araçlarında, öğrencilerin demografik bilgilerini ve öğrencilere ait tanımlayıcı istatistiklere ulaşılması amacıyla araştırmacı tarafından uzman görüşü alınarak oluşturulan "Kişisel Bilgi Formu" , öğrencilerin duygusal zekâ düzeylerini belirlemek için Küçükkaragöz ve Kocabaş (2012) tarafından geliştirilen "Çocuklar İçin Duygusal Zekâ Ölçeği" Kolb (1999) tarafından geliştirilen, Evin-Gencel tarafından (2007) türkçeye uyarlanan "Kolb'un Öğrenme Stilleri Envanteri –Versiyon III (KÖSE-III)", Benjanim Burdon (1955) tarafından geliştirilen "Burdon Dikkat Testi" ve Muris (2001) tarafından geliştirilen Telef (2012) tarafından türkçeye uyarlanan "Çocuklar İçin Öz-yeterlik Ölçeği" kullanılmıştır. Elde edilen veriler kodlanarak SPSS 25 paket programına aktarılmış, tanımlayıcı istatistikleri belirlemek için frekans ve yüzde dağılımlarına bakılmış, t-testi, çoklu doğrusal regresyon, pearson korelasyon analizi, MANOVA teknikleri kullanılmıştır. Yapılan analizler sonucunda; ortaöğretim öğrencilerinin duygusal zekâ puanlarına göre demografik bilgilerinin karşılaştırılmasında, cinsiyet, günlük internet kullanım süresi, algılanan akademik başarı düzeyine göre istatistiksel açıdan anlamlı farklılıklar olduğu görülmüştür. Öğrencilerin öz-yeterlik puanlarına göre demografik bilgilerin karşılaştırılmasında, cinsiyet, günlük internet kullanım süresi, algılanan akademik başarı düzeyine göre istatistiksel açıdan anlamlı farklılıklar olduğu görülmektedir. Öğrencilerin dikkat puanlarının demografik bilgilerine göre karşılaştırılmasında ise cinsiyet değişkeninde anlamlı farklılıklar olduğu görülmektedir. Öğrencilerin öğrenme stillerine göre karşılaştırılmasında, 89' unun yerleştirme, 153'ünün değiştirme, 65'inin ayrıştırma, 87'sinin özümseme öğrenme stiline sahip olduğu görülmüştür. Öğrencilerin duygusal zekâ puanlarının öz-yeterlik puanları ve dikkat puanları arasındaki yordayıcı gücüne bakıldığında, akademik öz-yeterlik ait toplam varyansın %24, sosyal öz-yeterlik ait toplam varyansın %23, duygusal öz-yeterlik ait toplam varyansın %29, dikkat düzeylerine ait toplam varyansın ise %3'ünün duygusal zekâ ile açıklandığı görülmektedir. Öğrencilerin duygusal zekâ puanları ile öz-yeterlik puanları arasındaki ilişkiye bakıldığında, (r= ,566) pozitif yönlü orta düzeyde bir ilişki olduğu görülmektedir. Dolayısıyla duygusal zekâ düzeyi arttıkça öz-yeterlik düzeyi de artmaktadır. Öğrencilerin dikkat puanlarının duygusal zekâ alt boyutları ve toplam puanı arasındaki ilişkiye bakıldığında, (r= ,109) pozitif yönlü düşük düzeyde bir ilişki olduğu görülmektedir. Dolayısıyla öğrencilerin duygusal zekâ puanı arttıkça dikkat düzeyi de artmaktadır. Elde edilen bulgular ilgili literatür ışığında tartışılmış ve önerilere yer verilmiştir.

The aim of this research is to examine the emotional intelligence levels, learning styles, attention and self-efficacy of middle school students who play sports and who do not. The universe of the research, T.C. Secondary school students in the coverage area of the Ministry of National Education, Kastamonu Provincial Directorate of National Education constitute the Ministry of National Education. From within the sample group of the research is based on the possibility of the universe in an easy way the method of sampling the sampling method, which is not Şehit Osman Yilmaz, Middle School, Secondary School, Şehit Necmi Yıldırım, Şehit Ayşe Aykaç boarding school, a martyr to studying in this school Project in Middle School in the academic year 2021-2022 Ansar 6,7 and 8. the class consists of students. In the light of this information obtained, the sample of the study was: 6,7 and 8 in the 2021-2022 academic year. of the 926 students studying in the classroom, there are 394 students selected by the easy sampling method. The data collection tool of the research, the descriptive statistics of the demographic information of the students and the students in order to achieve the expert opinion that is created by the researcher by taking "personal information form" , Kucukkaragoz students to determine their level of emotional intelligence and Kocabaş (2012) developed by "emotional intelligence scale for children" Kolb (1999) developed by the house-by Gencel (2007) adapted to Turkish Kolb's learning style inventory –Version III (KÖSE-III)", The "Burdon Attention Test" developed by Benjanim Burdon (1955) and the "Self-efficacy Scale for Children" adapted to Turkish by Peref (2012) developed by Muris (2001) were used. The data obtained were encoded and transferred to the SPSS 25 package program, frequency and percentage distributions were looked at to determine descriptive statistics, t-test, multiple linear regression, pearson correlation analysis, and MANOVA techniques were used. Analysis of results; scores on the emotional intelligence of Secondary School students comparison of demographic data, gender, daily internet usage time, statistically significant differences were seen according to the level of perceived academic achievement. Students ' self-efficacy scores for the comparison of demographic data, gender, daily internet usage time, there seem to be statistically significant differences according to the level of perceived academic achievement. In comparison of the attention scores of the students according to their demographic information, there are significant differences in the gender variable. Comparing the students according to their learning styles, it was seen that 89 of them had a placement learning style, 153 had a replacement learning style, 65 had a separation learning style, and 87 had an assimilation learning style. Emotional intelligence scores of students self-efficacy scores and scores between attention considering the predictive power of academic self-efficacy of the total variance of 24%, social self-efficacy of the total variance of the 23%, emotional self-efficacy, the total variance of the 29% of the total variance of the level of attention if it is 3% it is seen that with emotional intelligence are described. When the relationship between the emotional intelligence scores of the students and their self-efficacy scores is examined, it is seen that there is a positive and moderate relationship (r=,566). The relationship between emotional intelligence scores and self-efficacy scores of the students is examined decisively. Therefore, as the level of emotional intelligence increases, the level of self-efficacy also increases. Looking at the relationship between the emotional intelligence sub-dimensions and the total score of the students' attention Dec, it is seen that there is a low positive level relationship (r= ,109). Therefore, as the emotional intelligence score of the students increases, the level of attention also increases. The findings obtained have been discussed in the light of the relevant literature and suggestions have been given.
An investigation of emotional intelligence levels, learning styles, attention and self-efficacy of middle school students who play sports and do not play sports
Keywords: Duygusal zekâ; Spor; Öğrenme; Dikkat; Öz-yeterlik; Emotional intelligence; Sports; Learning; Attention; Self-efficacy